Clinical Characteristics, Comorbidities, Length of Stay, and Mortality of COVID-19 Patients in RSUD Cideres, Majalengka, West Java - Herry Garna; Dika Rifky Fernanda; Gibran Bramasta Dirgavansya; Heru Haerudin; Zulmansyah Zulmansyah; Samsudin Surialaga; Lelly Yuniarti (Universitas Islam Bandung, 2021)
Until now, the world is still facing the COVID-19 pandemic caused by SARS-CoV-2. The number of deaths of COVID-19 patients in Indonesia is quite large when compared to other countries. Clinical manifestations, comorbidities, length of stay, and the mortality of COVID-19 vary widely in each study. This study analyzes clinical characteristics, comorbidities, length of stay, and mortality of COVID-19 patients in RSUD Cideres, Majalengka, West Java. This study is an observational study with total sampling and purposive sampling. Subjects were patients with nasal swabs confirmed SARS-CoV-2 and hospitalized at RSUD Cideres from January to July 2021. Clinical manifestations, comorbidities, length of stay, and mortality of COVID-19 patients aged ≥17 years old, were extracted from medical records. Results showed that the majority of 213 COVID-19 patients were age 41–60 years 114 (53.5%), female 114 (53.5%), with an upper respiratory tract in 207 (97.1%), and shortness of breath in 203 (95.3%) patients. 153 (71.8%) patients had a fever, while headache, diarrhea, and anosmia respectively 49 (23.0%), 19 (8.9%), and 10 (4.6%), respectively. Vital signs were the Glasgow Coma Scale (GCS) normal in 190 (89.2%) patients. Most of patients had respiration rate >20/min in 201 (94.3%), oxygen saturation <90% in 98 (46.0%), and chest x-rays: bronchopneumonia 134 (62.9%) and pneumonia 23 (10.7%). Comorbidities were hypertension, diabetes mellitus, and chronic heart failure in 74 (34.7%), 56 (26.2%), and 46 (11.7%) patients, respectively. The length of stay who died for 1–7 days (22 patients) and 8–14 days (9 patients); means almost all patients (29 of 32) died during the length of stay for 1–14 days. In conclusion, the majority of COVID-19 patients at RSUD Cideres are female, aged 41–60 years, had upper respiratory tract/shortness of breath, GCS normal, saturation oxygen <90%, chest x-rays: bronchopneumonia and pneumonia, comorbidities: hypertension, and length of stay for patients who died 1–7 days. KARAKTERISTIK KLINIS, KOMORBITAS, LAMA RAWAT, DAN MORTALITAS PASIEN COVID-19 DI RSUD CIDERES, MAJALENGKA, JAWA BARATHingga saat ini, dunia masih menghadapi pandemi COVID-19 yang disebabkan oleh SARS-CoV-2. Jumlah kematian pasien COVID-19 di Indonesia cukup besar jika dibanding dengan negara lain. Manifestasi klinis, komorbid, lama rawat, dan mortalitas pasien COVID-19 sangat bervariasi pada setiap penelitian. Tujuan penelitian ini menganalisis karakteristik klinis, komorbiditas, lama rawat, dan mortalitas pasien COVID-19 di RSUD Cideres, Majalengka, Jawa Barat. Penelitian ini adalah penelitian observasional dengan total sampling dan purposive sampling. Subjek adalah pasien dengan nasal swab terkonfirmasi SARS-CoV-2 dan dirawat di RSUD Cideres periode Januari hingga Juli 2021. Data manifestasi klinis, komorbid, lama rawat, dan mortalitas pasien COVID-19 usia ≥17 diambil dari rekam medik. Hasil menunjukkan bahwa mayoritas 213 pasien COVID-19 berusia 41–60 tahun 114 (53,5%) dan wanita 114 (53,5%) dengan keluhan saluran napas atas 207 (97,1%) dan napas pendek 203 (95,3%) pasien. 153 (71,8%) pasien mengalami demam, sedangkan sakit kepala, diare, dan anosmia masing-masing 49 (23,0%), 19 (8,9%), dan 10 (4,6%) pasien. Tanda vital Glasgow Coma Scale (GCS) normal pada 190 (89,2%) pasien. Kebanyakan pasien mempunyai frekuensi napas >20/menit pada 201 (94,3%) pasien, saturasi oksigen <90% pada 98 (46,0%) pasien, serta rontgen toraks: bronkopneumonia pada 134 (62,9%) pasien dan pneumonia pada 23 (10,7%) pasien. Komorbid adalah hipertensi, diabetes melitus, dan chronic heart failure pada 74 (34,7%), 56 (26,2%), dan 46 (11,7%) pasien berturut-turut. Lama rawat pasien yang meninggal 1–7 hari (22 pasien) dan 8–14 hari (9 pasien), berarti hampir semua pasien (29 dari 32) meninggal selama rawat 1–14 hari. Simpulan, mayoritas pasien COVID-19 di RSUD Cideres adalah wanita, berusia 41–60 tahun, keluhan saluran napas atas/napas pendek, GCS normal, rontgen toraks: bronkopneumonia dan pneumonia, komorbid: hipertensi, serta lama rawat pasien yang meninggal paling banyak 1–7 hari.